Bank Customer Movement Intentions: Development of a Scale Based on the Quality of Customer Experience Clause andi s Success Model - Farhan Fauzi; Ignatius Hari Santoso (Journal of Accounting and Finance Management, 2024)
This research aims to analyze switching intention : scale development based on Klaus customer experience quality and IS Success Model. This research focuses on the variables system quality, information quality, service quality, product experience, moment of truth, and peach of mind. This research uses quantitative methods by processing primary data obtained through questionnaires from 57 people, using simple random techniques or sampling with the Slovin formula. Data obtained using Smartpls 4. The parameters tested in this research are validity test, reliability test, R-Square, and T test. Best on the results of research tests concluded: (1) System quality has significant and positive effect on switching intention, (2) Quality information has significant and positive effect on switching intention, (3) Quality of service has no significant and not positive effect on switching intention, (4) Product experience has no significant and not positive effect on switching intention, (5) Moment of truth has significant and positive effect on switching intention, (6) Peach of mind has significant and positive effect on switching intention.